Preparation of Mesoporous Silica-Supported Palladium Catalysts for Biofuel Upgrade - Ling Fei; Harvind Kumar Reddy; Joshua Hill; Qianglu Lin; Bin Yuan; Yun Xu; Peter Dailey; Shuguang Deng; Hongmei Luo (Journal of Nanotechnology)
We report the preparation of two hydrocracking catalysts Pd/CoMoO4/silica and Pd/CNTs/CoMoO4/silica (CNTs, carbon nanotubes). The structure, morphologies, composition, and thermal stability of catalysts were studied by X-ray diffraction (XRD), scanning electron microscopy (SEM), Raman spectroscopy, transmission electron microscopy (TEM), energy-dispersive X-ray (EDX), and thermogravimetric analysis (TGA). The catalyst activity was measured in a Parr reactor with camelina fatty acid methyl esters (FAMEs) as the feed. The analysis shows that the palladium nanoparticles have been incorporated onto mesoporous silica in Pd/CoMoO4/silica or on the CNTs surface in Pd/CNTs/CoMoO4/silica catalysts. The different combinations of metals and supports have selective control cracking on heavy hydrocarbons.